2001
DOI: 10.1093/rheumatology/40.5.528
|View full text |Cite
|
Sign up to set email alerts
|

A brief screening tool for knee pain in primary care. 1. Validity and reliability

Abstract: The KNEST appears to be a reliable and valid composite tool for the study of population needs and outcomes of care for people aged over 55 yr with knee pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 22 publications
5
50
2
Order By: Relevance
“…Pain occurrence, number and location of pain sites Our measure of the occurrence of self-reported pain was based on a single question and an associated body manikin, a method used frequently in self-reported health surveys [32][33][34]. Participants were asked, ''In the past four weeks have you had any pain that has lasted for one day or longer in any part of your body?''…”
Section: Health Survey Questionnairementioning
confidence: 99%
“…Pain occurrence, number and location of pain sites Our measure of the occurrence of self-reported pain was based on a single question and an associated body manikin, a method used frequently in self-reported health surveys [32][33][34]. Participants were asked, ''In the past four weeks have you had any pain that has lasted for one day or longer in any part of your body?''…”
Section: Health Survey Questionnairementioning
confidence: 99%
“…In self-report health surveys, they are often included as a simple screening instrument to assess the location of pain or to estimate the prevalence of pain in certain body areas. [1][2][3] Subjects are usually asked to shade their pain within the outlines of front and back views of a blank body manikin. The presence or absence of pain is assessed by placing a transparent template, divided into a number of defined body areas, over the completed pain drawing, and observing any shading within these areas.…”
mentioning
confidence: 99%
“…Previous studies have found good test-retest reliability of completion of pain drawings by subjects in different settings. [2][3][4][5][6] Completed pain drawings can also be used to determine the presence of widespread pain according to a predetermined definition. 7 In population surveys, scoring of completed pain drawings is often performed manually by a data entry clerk, although for a large survey, it would not be cost-effective (either in time or burden on staff) to use a single rater.…”
mentioning
confidence: 99%
“…A previously validated questionnaire for OA patients enquiring about their use of services and self-management [the modified Knee Pain Screening Tool (KNEST) 169 ], with a selection of items that measure care related to NICE guidance topics. ii.…”
Section: Process Measures Of Implementation Of the Mosaics Model-of-carementioning
confidence: 99%
“…A range of secondary outcomes were collected: the proportion of treatment responders using the internationally agreed OMERACT clinical responder criteria 200,201 that combine data on pain and function from the WOMAC 228 with patient's global assessment of change (recorded using a 6-point Likert scale); physical activity levels (PASE, which assesses physical activity levels over a 1-week period combining physical activity from several domains including household, occupational and leisure); 169 self-reported BMI (calculated from self-reported height and weight); exercise adherence (attendance at treatment sessions, self-reported adherence to prescribed exercise programme); use of local physical activity facilities in the previous 7 days (single item); a modified version of a measure of treatment acceptability and credibility; 234,235 ). Resource use and EQ-5D-3L data were used in the cost-utility analysis (further details are provided in Health economic analysis).…”
Section: Secondary Outcomesmentioning
confidence: 99%